The Effect of Brand Image of Food and Beverage Products by People with Disabilities on Sales Volume of KUBE “BISA” PERPENCA - Asrorul Mais; David Kristian Susilo; Hanif Hadinata Utama (Cita Konsultindo Research Center, 2023)
This study aims to determine the effect of brand image on sales volume in KUBE “BISA” PERPENCA joint business group where most of its members have disabilities, whether the level of product sales can increase by using a brand image strategy. In this study, researchers used a qualitative descriptive method, where researchers collected, reviewed, and described the results of the field research to determine the effect of brand image on KUBE